2016
DOI: 10.13075/ijomeh.1896.00657
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vitamin D status among Jordanian employees: Focus on the night shift effect

Abstract: Objectives: To assess the association between night work and 25-hydroxy vitamin D (25OHD) levels, and to evaluate effect of potential risk factors on 25OHD levels. Material and Methods: A total of 140 adult Jordanian employees were recruited. Demographic, lifestyle and working patterns data were documented through a well-structured questionnaire. Vitamin D status was assessed by measuring circulating concentrations of 25OHD. Results: Mean 25OHD level was 23.8 ng/ml. No significant difference was found in 25OHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…Mizoue et al [ 28 ] found low 25(OH)D concentrations more frequent in young, female, and smokers, engaged in shiftwork and overtime work. Alefishat and Farha [ 29 ] evaluated vitamin D status in female night workers that showed significantly lower serum 25(OH)D levels compared to the female day workers ( p =0.01). The number of night shifts/month was negatively correlated with 25(OH)D levels in both the males and females ( p =0.01 and p =0.007).…”
Section: Resultsmentioning
confidence: 99%
“…Mizoue et al [ 28 ] found low 25(OH)D concentrations more frequent in young, female, and smokers, engaged in shiftwork and overtime work. Alefishat and Farha [ 29 ] evaluated vitamin D status in female night workers that showed significantly lower serum 25(OH)D levels compared to the female day workers ( p =0.01). The number of night shifts/month was negatively correlated with 25(OH)D levels in both the males and females ( p =0.01 and p =0.007).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that subjects with the adequate serum 25(OH)D concentration and high vitamin D intake have a more favorable lipid profile than those with vitamin D deficiency [3,22,41,[43][44][45][46]. The most often observed changes include a vitamin D-induced decrease in triglycerides and an increase in HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial correlations were found mainly among individuals with BMI ≥30 kg/m 2 . The most probable explanation for the significant results limited to persons with excess weight may be the fact that obesity is often associated with lower 25(OH)D concentrations in comparison to normal-weight individuals [22,29,30]. The most important relationship was observed in the context of blood pressure regardless of gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, conversation with control room employees revealed that they generally prefer to go outdoors for sunlight exposure due to their nature of work in dark environments. These factors probably offset the higher risk of vitamin D deficiency in control room workers due to night shifts [26,27] Night shift workers, due to their working hours and daytime sleeping, are generally exposed less to solar UV-B irradiation [28].…”
Section: Discussionmentioning
confidence: 99%